Cycling tourism and cycling sport events tourism on the Estrada Parque Piraputanga/ Mato Grosso do Sul, Brazil: possibilities for local development - Romero Bandeira Serrou Camy , Larissa; de Oliveira Belino Bonfim, Izac; Scheuer, Luciane (Cenário: Revista Interdisciplinar em Turismo e Território, 2023)
Cycling is a sports and leisure activity with accelerated growth throughout the national territory. In Brazil, there is a lack of data denoting the economic potential of this sport modality, as well as the sectors indirectly affected, such as tourism. From this assumption, this research had as a general objective to identify the perception of cyclists about the tourism potential of APA Estrada Parque Piraputanga, an Environmental Protection Area, for the development of cycling tourism and cycling sport events tourism. The procedures used initially in this investigation were based on a bibliographic research and documental analysis, followed by an exploratory analysis in loco. After initial procedures, this research was based on a quali-quantitative approach, with the application of an on-line questionnaire with cyclists using the snowball technique. The questionnaire had closed and open questions, which were analyzed by simple sampling, as well as the application of the technique of Content Analysis (CA) of Bardin (2011) for the open question. As result, in the perception of the cycle tourists there is need for investment in improving the infrastructure for tourism in general. Finally, it was detected that APA Estrada Parque Piraputanga has potential for local development through the segment of cycling tourism and cycling sport events tourism.